Dipturus batis - Carneiro, Miguel; Martins, Rogélia; Landi, Monica; Costa, Filipe O. (Zenodo, 2014)
* Dipturus batis (Linnaeus, 1758) – Blue skate; Raia-oirega, Airoga, Arrai or Raia Based on morphological analyses and on molecular phylogenetic relationships, Iglésias et al. (2010) revealed the existence of four distinct species in the northeastern Atlantic (namely D . cf. flossada , D . cf. intermedia , D . oxyrinchus and D . nidarosiensis ). The records of D. batis off mainland Portugal, off the Azores and off Madeira can only be reclassified upon the formal revision of the Dipturus species from the northeastern Atlantic, and taking into consideration the resurrections and the fully documented re-descriptions of both Dipturus sp. cf. flossada (Risso, 1826) and of Dipturus sp. cf. intermedia (Parnell, 1837). Therefore, the species D. batis was not counted in the total number of species in the current list. Published as part of Carneiro, Miguel, Martins, Rogélia, Landi, Monica & Costa, Filipe O., 2014, Updated checklist of marine fishes (Chordata: Craniata) from Portugal and the proposed extension of the Portuguese continental shelf, pp. 1-73 in European Journal of Taxonomy 73 on page 15, DOI:10.5852/ejt.2014.73, http://zenodo.org/record/3866515